2017
DOI: 10.3349/ymj.2017.58.1.139
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Robotic Colonoscopic Manipulation System, Using Haptic Feedback Algorithm

Abstract: PurposeColonoscopy is one of the most effective diagnostic and therapeutic tools for colorectal diseases. We aim to propose a master-slave robotic colonoscopy that is controllable in remote site using conventional colonoscopy.Materials and MethodsThe master and slave robot were developed to use conventional flexible colonoscopy. The robotic colonoscopic procedure was performed using a colonoscope training model by one expert endoscopist and two unexperienced engineers. To provide the haptic sensation, the inse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…This robot also had a haptic feedback function. The robot enables colonoscope's insertion up to 1.5 m, rotation of 360 degrees, and tilting up to a ± 180°angle [10].…”
Section: Robot-assisted Flexible Eendoscopymentioning
confidence: 99%
“…This robot also had a haptic feedback function. The robot enables colonoscope's insertion up to 1.5 m, rotation of 360 degrees, and tilting up to a ± 180°angle [10].…”
Section: Robot-assisted Flexible Eendoscopymentioning
confidence: 99%
“…The master robot is equipped with a tilting and an insertion/rotation device. The system is built with kinesthetic and haptic algorithm, and it does not require direct contact of the operator with the endoscope [16]. The slave robot has a range of motion same as that of the flexible endoscope.…”
Section: Technology Solutions For Advanced Endoscopymentioning
confidence: 99%
“…The system can be adapted to a standard colonoscope by mounting it on the slave robot. A previous study showed that an expert endoscopist could complete the insertion of this robotic endoscope within 15 to 20 minutes, with 100% success rate [16]. Development of this system, however, is ongoing.…”
Section: Technology Solutions For Advanced Endoscopymentioning
confidence: 99%
“…They need careful clinical evaluation and should be tailored to specific clinical needs. In some cases, e.g., patients with acute coronary syndrome or high-syntax score lesions, special evaluation is needed for applying a robotic system [11][12][13]. Therefore, a master-slave robotic system for VIR is necessary for minimization of the radiation exposure to operators.…”
Section: Introductionmentioning
confidence: 99%